Halogenated 1-Hydroxynaphthalene-2-Carboxanilides Affecting Photosynthetic Electron Transport in Photosystem II - Gonec, Tomas; Kos, Jiri; Pesko, Matus; Dohanosova, Jana; Oravec, Michal; Liptaj, Tibor; Kralova, Katarina; Jampilek, Josef (Molecules (Basel, Switzerland), 2017)
Series of seventeen new multihalogenated 1-hydroxynaphthalene-2-carboxanilides was prepared and characterized. All the compounds were tested for their activity related to the inhibition of photosynthetic electron transport (PET) in spinach (Spinacia oleracea L.) chloroplasts. 1-Hydroxy-N-phenylnaphthalene-2-carboxamides substituted in the anilide part by 3,5-dichloro-, 4-bromo-3-chloro-, 2,5-dibromo- and 3,4,5-trichloro atoms were the most potent PET inhibitors (IC50 = 5.2, 6.7, 7.6 and 8.0 µM, respectively). The inhibitory activity of these compounds depends on the position and the type of halogen substituents, i.e., on lipophilicity and electronic properties of individual substituents of the anilide part of the molecule. Interactions of the studied compounds with chlorophyll a and aromatic amino acids present in pigment-protein complexes mainly in PS II were documented by fluorescence spectroscopy. The section between P680 and plastoquinone QB in the PET chain occurring on the acceptor side of PS II can be suggested as the site of action of the compounds. The structure-activity relationships are discussed.
Keywords: Photosynthesis; Photosystem II Protein Complex; photosynthetic electron transport (PET) inhibition; hydroxynaphthalene-carboxamides; Electron Transport; spinach chloroplasts; naftoly; inhibiční koncentrace 50; structure-activity relationships; transport elektronů; Chloroplasts; Naphthols; Inhibitory Concentration 50; fotosyntéza; chloroplasty; fotosystém II (proteinový komplex); Spinacia oleracea